Anaerobic co‐digestion of cow manure and barley: Effect of cow manure to barley ratio on methane production and digestion stability. Issue 2 (28th September 2015) - Akyol, Çağrı; Ozbayram, Emine Gozde; Ince, Orhan; Kleinsteuber, Sabine; Ince, Bahar
Abstract : Anaerobic co‐digestion of cow manure (CM) and barley (Hordeum vulgare, HV) was evaluated in terms of biochemical methane potentials with respect to five different CM to HV mixing ratios of 1:0, 2:1, 1:1, 1:2, and 0:1 based on volatile solids (VS) contents. Bacterial community composition of the seed sludge was examined using 454 pyrosequencing of 16S rRNA gene sequences. Based on the taxonomic classification, major bacterial phyla belonged to the Firmicutes (42%) and Bacteroidetes (22%). Co‐digestion of CM and barley was superior at all mixing ratios when compared with the digestion of CM alone. The digestion systems failed at the ratio of 0:1, and there was no methane production. The presence of barley caused high acidification, but there was no volatile fatty acids accumulation at the end of the digestion. Highest specific methane productions were obtained at CM to HV mixing ratios of 2:1 and 1:1 as 216 CH4 /g VS and 230 CH4 /g VS, respectively. Because of the highest specific methane production, the optimal CM to HV mixing ratio was found to be 1:1 in this study. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 589–595, 2016